Atmospheric temperature sounding on Mars, and the climate sounder on the 2005 reconnaissance orbiter - Taylor, F; Calcutt, S; Read, P; Lewis, SR; McCleese, D; Schofield, J; Zurek, R (2006)
Detailed measurements of the vertical profiles of atmospheric temperature, water vapour, dust and condensates in the Martian atmosphere are needed to characterize the present-day Martian climate and to understand the intricately related processes upon which it depends. Among the most important of these are accurate and extensive temperature measurements. Progress to date, key problems still to be addressed and upcoming new approaches to the measurement task are briefly reviewed, and expectations for the Mars Climate Sounder experiment on the 2005 Mars Reconnaissance Orbiter are described. Some even more advanced methods for temperature, humidity and condensate sounding in the decade beyond MCS/MRO, and promising approaches to achieving these are also considered. (c) 2006 Published by Elsevier Ltd on behalf of COSPAR.